(3ObGFb GdefgGLs - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3HdHjS s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO agPG cJGH ajg TQM ObGFb CdaGX GdefgGL hGdaQb Hjf CdaGXg hCdaGX GdeMQQ ddEeGe GdQGaYi s
(3BNQgG (B:s
(3hGdCUM HWdGf GdaGSO HLfhf GdSjO hEZGFg adaXI EZeGFI RjGOI dg hGddg CYde fLR GdOaGFa Ydi GdefgGL ddfhhi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
Keywords: (3Gdabg GdTGaYjs